Pelestarian Kesenian Debus Banten di Padepokan Maung Pande - Yosef Calasanza; Gunawan (Sasdaya: Gadjah Mada Journal of Humanities, 2023)
Debus is one of the popular arts in Banten society. During the Banten kingdom, in the past Debus art became well-known. Initially, Debus became a medium for spreading Islam in Banten. During the colonial period, debus used against colonial troop. Debus perpetrators who are aware of their immunity to sharp weapons and bullets form a force to confront the colonial army. After independence, Debus developed into an art that is often staged in various events at the regional and national levels. However, recently its popularity has waned. Debus art is not much staged and known in the community. This circumstance has prompted Banten hermitages to promote and preserve Debus arts. This article aims to describe the activities of the hermitage in maintaining the existence of debus as well as activities to preserve the Banten debus art by Padepokan Maung Pande. The data collection method was carried out using qualitative research methods by focusing on data collection on member of the Maung Pande hermitage. The results of the study show that the conservation efforts carried out by the Maung Pande hermitage are carried out by collaborating with schools in Banten province.